A STUDY ON ENGLISH PRIVATE TUTORING BASED ON STUDENTS’ PERCEPTIONS AT SMP XAVERIUS 1 BANDAR LAMPUNG - Yanuar Dwi Prastyo; Monica Vidya Tinanti; Siti Farhana (STKIP Persada Khatulistiwa Sintang, 2022)
The purpose is to obtain facts and experiences that occur to students when using English private tutoring in their learning system which is described in detail using a descriptive method through perceptions from students at SMP Xaverius 1 Bandar Lampung. Private tutoring is needed for students to get more learning in the lack condition of Covid-19 and can give more benefits to improving their skill and their progress. This journal used the qualitative method. To collect the data used questionnaires and interviews. The results of this study indicate that there are several types of perceptions given by students based on what happens when using English private tutoring and are divided into four different categories in the grouping of student perceptions, comparison between school & tutoring, financial aspects, learning model system, and students' academic & quality level. The results showed positive perceptions of students and tutors.